Ocupação, atividade e efeito da caça de tatu-bola Tolypeutes tricinctus na Caatinga, Nordeste do Brasil - Liana Mara Mendes de Sena (2020)
Among armadillos, the Brazilian-three-banded-armadillo Tolypeutes tricinctus is the only endemic species of Brazil, found predominantly in the Caatinga dry forest and some areas of the Cerrado savanna. Unlike the other armadillos, T. tricinctus can flex its carapace assuming the shape of a ball, which provide protection against natural predators, but it makes it more vulnerable to human capture. Due to illegal hunting and habitat loss, the species is classified as endangered, and has probably largely disappeared from its original distribution. Also, is a poorly known armadillo, with scarce scientific information about its ecology and occurrence. In this study, we investigated the frequency of seized of armadillos and other wild mammals in the environmental notices of violation reports in the state of Piauí, northeastern Brazil. Assuming that hunting is one of the main threat to the armadillo and the biggest management challenge for protected areas in the State of Piauí, we conducted a camera trap survey between January and September 2018 at Serra da Capivara National Park, a priority area for conservation of the Caatinga. We aimed to investigate how environmental and anthropic factors influence the occupation, detection and activity pattern of T. tricinctus. To achieve these goals, we evaluated environmental notices of violations reports from the federal agencies about seizure mammals in the Piauí State, from 2008 to 2018. Using absence-presence data, we evaluated how environmental and anthropic factors affect the occupancy and detectability probabilities based on the Akaike Information Criterion. Also, we describe the daily activity patterns of T. tricinctus and test the overlap in daily activity between their potential competitors and predators using circular and overlapping analyses. Armadillos were the most poached species, representing 89,2% of seized mammals. D. novemcinctus, followed by T. tricinctus are the main target. We obtained 118 independent records of T. tricinctus resulting in a naïve occupancy of 0,49 from 9,801 camtrap-days. T. tricinctus occupancy was positively influenced by vegetation cover (NDVI, w+=0,61). Also, we found a positive relationship between the probability of detection and effort (w+=0,82) and detection was higher (w+=0,72) in the dry season than in rain season. The temporal patterns of T. tricinctus was crepuscular and nocturnal, and its nocturnality decreased in the presence of large felids. This results indeed the high pressure of poaching on armadillos, evident pattern throughout the Teresina capital and southeastern pf State of Piauí. The occupancy modeling showed that T. tricinctus occupies environments with denser forest cover, and that it tolerates moderate anthropic influence in a forest landscape. We emphasize the need for future research for better planning of local conservation interventions involving poaching, subsistence, and illegal trade, in order to guarantee the long-term persistence of T. tricinctus.